Calculating and Evaluating of the Achievements of Pharmaceutical Separation Engineering Course for Pharmaceutical Engineering Major Based on Engineering Education Certification - Li, Hua; Shi, Xiaohua (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim: This study aims to evaluate the efficiency of the achievement degree for engineering education certification, example as pharmaceutical separation engineering course. The calculating method of achievement degree about graduation requirement in engineering education certification in colleges and universities was introduced in this paper. Materials and Methods: A total 53 students were selected from the exam of pharmaceutical separation engineering course and the total score of the exam is 100. Among them, objective total score: 70, subjective total score: 30. The calculation of course achievement degree is realized by Excel tool. Results: In order to make the evaluation process of achievement degree more reasonable, not only the graduation requirements and course achievement degree were calculated with Excel and statistical analysis and graphical analysis on the calculation results of course achievement degree were made, but also the achievement of course objectives and existing problems were analyzed and evaluated. For the students who need to pay attention to, it is necessary to analyze whether there are any problems that deviate from the focus and other problems in course learning, so as to help them overcome the problems in the follow-up study. Conclusion: This method is really student-centered and provides necessary information for teachers to revise and improve the teaching of courses at any time.
Keywords: Professional certification; Graduation requirements; Achievement Degree; Excel